Care provided by a non-specialist oncology nurse to hospitalized cancer patients: An integrative Review (Research, Society and Development, 2021)
Cancer is characterized by uncontrolled growth and the spread of abnormal cells in the body, the causes of which may be associated with external or internal factors with increasing incidence. Thus, health professionals still sin in care due to the lack of knowledge in the management of the disease. Objective: To identify the available scientific evidence on the care provided by a non-specialist oncology nurse to hospitalized cancer patients. Methodology: This is an integrative review, using four databases: Pubmed, Scielo, Cinahl, and Lilacs for the selection of studies in Portuguese, English and Spanish, from the years 2008 to 2018. Results: It constitutes a final sample of nine articles. After analysis, the following categories emerged: interventions in chemotherapy treatment; care for tumor wounds; comfort to the patient/family; meeting the specific needs of the client; search for quality of life for cancer patients; spiritual/religious, emotional support; elaboration of care and terminological subset to improve the nursing process; seeking to minimize pain related to tumor wounds; palliative care, prevention of suffering and reframing of care management. Conclusion: Non-specialist nurses perform various cancer care. However, they are unaware of their role as agents of change, characterizing gaps in this theme. This research is relevant for Nursing, as it minimizes dichotomies between theory/practice and clients' quality of life. Permanent Education stands out as a powerful tool for qualifying and optimizing care. The need for further research and studies is emphasized.